TRADITION AND MODERNISM IN YORUBA ARCHITECTURE: Bridging the Chasm - Sonaiya, Olusola A.; Dincyurek, Ozgur (Open House Int, 2009)
Vernacular and modem architecture hove mostly been seen as antitheses, impossible to reconcile, especially in Africa. They appear to belong to different ages, utilize different materials and methods, and encourage or support different lifestyles. This paper aims of seeking points where a merging of principles may be attempted between the two positions. The study is based on a survey on the traditional architecture of the Yoruba people of West Africa. The decline in popular use of this building tradition and its rejection by design practitioners raises some physical and psychological issues which ore examined in this paper. These include: spatial layout, use and quality, ecology and economy, concepts, meaning and perception. The fate of Yoruba traditional built culture depends on a conscious attempt to reconcile it with peopled contemporary needs, lifestyles and world views. Therefore, a brief introduction on the importance of Yoruba architecture and its preservation will be followed by a general definition of its features and characteristics, advantages and disadvantages. Finally, the problems posed by the architecture modem trends in Yoruba land will be examined. It is hoped that such works may assist in the development of a truly responsive and sustainable architecture for the Yoruba people. The proposed solutions may be applied in other parts of Africa, or in regions with similar cultural or geographical concerns.
Keywords: Traditional Architecture; Yoruba Culture; Sustainability; Inadequacies of Modernism; Appropriate Design